Design of Expert System for Managing the System of AthTharthar Lake - Hala Mohammad Mohy; Basim Sh. Abed (Journal of Engineering, 2019)
The operation and management of water resources projects have direct and significant effects on the optimum use of water. Artificial intelligence techniques are a new tool used to help in making optimized decisions, based on knowledge bases in the planning, implementation, operation and management of projects as well as controlling flowing water quantities to prevent flooding and storage of excess water and use it during drought.